Assessment of Road Rehabilitation in Ibadan, Nigeria - Adewale Yoade; Samson Olaitan Olanrewaju; Sesan Adeniyi Adeyemi (Indonesian Journal of Geography, 2020)
The study examined road rehabilitation in Ibadan North East Local Government of Oyo State, Nigeria. The data used in this study was obtained from both primary and secondary sources. The primary data was obtained through a reconnaissance survey and administration of the questionnaire. The reconnaissance survey is appropriate to establish the nature of an environment, event or situation before making decisions. The population for this study consists of all the residents available in Ibadan north local government. Both descriptive and thematic content analysis was employed in the analysis. Findings showed that rehabilitation (3.33) is the most desirable facility in the study area. Construction, maintenance, traffic management capacity building and street naming followed with 3.01, 2.56, 2.42, 2.28 and 2.12, respectively. The study concluded that compensation is an important factor that can enhance sustainable urban renewal programme, and therefore resident whose building was affected are to be compensated so that they could secure a better place for living or for their transaction.